2012
DOI: 10.1007/s12522-012-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation, in vitro fertilization (IVF) and in vitro development (IVD) protocols for inbred BALB/cJ mice in comparison with outbred NMRI mice

Abstract: Superovulation with 48 h G-interval and using T6 during all in vitro procedures produces embryos more efficiently for NMRI mice than for BALB/cJ mice. For BALB/cJ mice, a protocol including superovulation with a 44-46 h G-interval, using mHTF during IVF and G1V/G2V medium during IVD, may improve in vitro embryo production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…In contrast to previous reports, 8,27,44 we show here that VDD alone (without hypocalcemia) did not reduce sperm cell motility, regardless of the severity of VDD. We therefore reinforce the idea that the previously reported reduction in sperm motility in VDD cases was likely a calcium‐mediated effect, as suggested 8,27‐49 . The results of our experiments are therefore in complete agreement with Sun et al 27 who demonstrated that VDD is accompanied by decreased extracellular calcium and phosphorus levels and that defective sperm motility in these situations can be overcome by calcium and phosphorus supplements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to previous reports, 8,27,44 we show here that VDD alone (without hypocalcemia) did not reduce sperm cell motility, regardless of the severity of VDD. We therefore reinforce the idea that the previously reported reduction in sperm motility in VDD cases was likely a calcium‐mediated effect, as suggested 8,27‐49 . The results of our experiments are therefore in complete agreement with Sun et al 27 who demonstrated that VDD is accompanied by decreased extracellular calcium and phosphorus levels and that defective sperm motility in these situations can be overcome by calcium and phosphorus supplements.…”
Section: Discussionsupporting
confidence: 93%
“…For induction of superovulation, female mice (weight 25‐30 g) received 10 IU of pregnant mare's serum gonadotropin (PMSG; Pregnecol, Armidale, Australia). After 48 hours, they were treated with 10 IU of human chorionic gonadotropin (hCG; Pregnyl, Tehran, Iran) 31 . In addition, in each group, five superovulated plugged positive females were used on day 3.5 after hCG injection to assess in vivo rate of blastocyst formation.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the treatment period (day 21), mature NMRI female mice were superovulated by intraperitoneal injection of 7.5 IU pregnant mare serum gonadotropin (PMSG) (Sigma‐Aldrich) followed by the administration of 7.5 IU human chorionic gonadotropin (HCG) (Sigma‐Aldrich) 48 hours later . Ovulation occurred within 14 hours of post‐HCG injection.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are, however, compatible with those described by Van der Auwera et al [23], reinforcing that the superovulation impact occurs not only at a later stage of development but also that the embryo reduction occurs soon after superovulation. Genetic alterations among the strains used may also contribute to variable responses to superovulation, fertilization levels [34] [35] and incubation rates. Fertilization rates can be easily determined when embryos are collected at 0.5 dpc by considering the total number of oocytes/1-cell embryos and allowing passage to a 2-cells stage or detecting pronucleus under the microscope.…”
Section: Discussionmentioning
confidence: 99%